Self-directed learning mathematics with V-Mindmap / Lim Ai Hui ... [et al.] - Lim, Ai Hui; Mohd Nawawi, Ahmad Afif; Choo, Hui Nee; Zainul Abidin, Nurul Amani; Kamilin, Muhammad Hafiz (Universiti Teknologi MARA, Kedah, 2023)
The V-Mindmap tool is a novel approach to teaching and learning Mathematics that includes instructional videos and tutorial questions based on the Four-Semester System (SES) syllabus in the Matriculation Programme for the academic session 2022/2023. Developed using the Directed Creative Process Model application, the V-Mindmap tool aims to assist matriculation students in learning Mathematics and to stimulate self-directed learning. It has been evaluated by a sample of 104 SES students (academic session 2022/2023), with four factors used to measure its effectiveness: presentation, efficiency, ease of use, and reliability. The results indicate that the V-Mindmap tool has been positively received by the respondents, with a minimum value of 3.25. Additionally, by providing a novel and effective tool for learning Mathematics, the V-Mindmap tool has the potential to benefit society by producing students who are better equipped to apply mathematical concepts in their future endeavours. The V-Mindmap tool aims to promote self-directed learning and the concept of a "flipped classroom" in the new norm, and represents an innovative approach to Mathematics education that could have far-reaching implications for the Matriculation Programme and beyond. The positive results of the evaluation, coupled with the copyright registration, suggest that the V-Mindmap tool has significant commercialization potential in the education market, which could be further explored to promote the tool's widespread use and adoption. With its innovative approach to teaching and learning Mathematics, the V-Mindmap tool has the potential to produce a new generation of mathematically competent students who can contribute positively to society in a wide range of fields.